2011
DOI: 10.1016/s2255-4971(15)30195-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Results From Arthroscopic Repair on Rotator Cuff Injuries Among Patients Under 50 Years of Age

Abstract: Objective: To assess the results from arthroscopic surgical treatment of rotator cuff injuries among patients under 50 years of age. Methods: Sixty-three patients with rotator cuff injuries who underwent arthroscopic surgical treatment performed by the Shoulder and Elbow Group of the Department of Orthopedics and Traumatology, in the Fernandinho Simonsen wing of Santa Casa Medical School, São Paulo, between August 1998 and December 2007, were reassessed. The study included all patients with rotator cuff injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Trauma is another reported cause of re-injury of the rotator cuff. 7 , 15 , 16 , 17 In a study assessing 63 patients under 50 years old, an age group in which trauma is more prevalent as an RCI trigger, Miyazaki et al 18 observed that trauma was the cause of two out of the four re-ruptures, with an interval from eight to 24 weeks after the first surgery. In the present sample, trauma was informed by the patients as the causative factor of the recurrence of symptoms and consequent re-injury of the rotator cuff in six cases (33.3%): three of them (50%) by fall on the limb and three (50%) by moving the limb beyond bearable.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is another reported cause of re-injury of the rotator cuff. 7 , 15 , 16 , 17 In a study assessing 63 patients under 50 years old, an age group in which trauma is more prevalent as an RCI trigger, Miyazaki et al 18 observed that trauma was the cause of two out of the four re-ruptures, with an interval from eight to 24 weeks after the first surgery. In the present sample, trauma was informed by the patients as the causative factor of the recurrence of symptoms and consequent re-injury of the rotator cuff in six cases (33.3%): three of them (50%) by fall on the limb and three (50%) by moving the limb beyond bearable.…”
Section: Discussionmentioning
confidence: 99%
“…In the period evaluated, 712 original articles were published in the Brazilian Journal of Orthopedics and 588 in Acta Ortopédica Brasileira, or 1300 publications. Among these, 84 (6.7% of the total) were clinical articles on shoulder diseases; 25 publications (1.9% of the total) 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 evaluated the clinical results of treatment of rotator cuff tears ( Table 1 ); twenty studies (80%) were case series (level of evidence IV), one (4%) case–control study (level of evidence III) and four (16%) cohorts (level of evidence II). No randomized study was published in the period.…”
Section: Resultsmentioning
confidence: 99%
“…Aging is a major prognostic indicator of tendon degeneration[ 31 ]. The vast majority of rotator cuff ruptures occur in middle-aged and older patients[ 32 , 33 ]. Previous studies have shown that the prevalence of rotator cuff injuries increases with age, reaching 50% by the 8 th decade of life[ 31 ].…”
Section: Discussionmentioning
confidence: 99%